Fisiologia do Phytophthora palmivora (Butl) BUtl II : Tensão na água como fator na produção de zoósporos - Gomes Medeiros, Arnaldo (Revista Ceres, 2025)
Regarding the little knowledge on physiology of zoosporangia indirect germinationin genus Phytophthora, was studied the conjugated action of relative air humidity and fluctuation of water temperature in zoospores production, in Phytophthora Palmivora (Butl.) Butl. Thus was estimated the quantily of zo- osporangia indirectly germinated in water after 2 hours, with the following treatment:-absenceand presence of thermic shock at 109C for 5', returning to the laboratory conditions at 259C. Zoosporangia under these treatments were reportedto stay for 12, 24, 36, 48, 60, 72, 84 and 96 hours in a confined room, carbon dioxide free and with 100, 90, 80 and 70% of relative humidity. It was found that relative air humidity regulates physiological maturation and time of indirect zoosporangia germination, not exceeding more than 72 hours, Thermic shock in water is dispensable for zoosporangia germination when preceeded by dehydration. The water stress variation is apparently essential to break zoosporangia dormancy.